SULTAN MUHAMMAD SYAFIUDDIN II: Pemimpin Kharismatik dari Ujung Utara Borneo Barat - Jaelani Jaelani (Khatulistiwa, 2014)
The interesting from the leadership of Sultan Muhammad Syafiuddin II is the attitude of humble, simple, and care about the small people have filled the space personality. Characteristics such, also colored pattern shown leadership and a form of devotion to the spiritual values of Islam. In this sense Sultan Muhammad Syafiuddin II is seen as a charismatic leader. Charismatic leadership shown Sultan Muhammad Syafiuddin II has spawned a positive influence on people. Thus leaving memories about the personality and policies on moral grounds are well maintained in folklore, a pilgrimage to the tomb, and store photos or images as sacred. This study will reveal the biography, the concept and vision of leadership that make up the character of Sultan Muhammad Syafiuddin II as a charismatic leader.